2020
DOI: 10.21037/gs.2020.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and women’s age on the prevalence of parathyroid failure after total thyroidectomy for multinodular goiter

Abstract: Background: Female gender, particularly of a young age, has been reported as a risk factor for hypocalcemia after total thyroidectomy. There are no studies, however, addressing specifically the influence of women's age and menstrual status on postoperative parathyroid function.Methods: Cohort study of consecutive patients undergoing total thyroidectomy for benign goiter between 2000-2017, excluding those with associated hyperparathyroidism, reoperation or conservative procedures.Prevalence of postoperative hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Villarroya-Marquina et al described female patients younger than 45 years of age and low PGRIS score as independent variables in predicting post-operative hypocalcemia in patients with MNG. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…Villarroya-Marquina et al described female patients younger than 45 years of age and low PGRIS score as independent variables in predicting post-operative hypocalcemia in patients with MNG. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…In one way or another, these result in some kind of injury to the parathyroid glands (fragmentation, thermal injury, devascularization, inadvertent resection, autotransplantation into the sternocleidomastoid muscle). The only exception might be the higher prevalence of hypoparathyroidism syndromes in young women in whom, besides an iPTH drop, other endocrine regulators such as the estrogens may play a role, particularly in total thyroidectomy for benign disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Villaroya‐Marquina and colleagues ( 26 ) evaluated 811 patients undergoing total thyroidectomy for benign goiter and reported that premenopausal women developed a higher prevalence of chronic hypoparathyroidism than men despite similar number of parathyroid glands remaining in situ at the end of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Published studies have reported the prevalence of chronic hypoPT to range from 6.4–37/100,000 population in different countries. ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ) Incidence has been more difficult to estimate, with only two studies reporting this to be between 0.8/100,000/year in hospitalized patients in Denmark and 2.6/100,000/year in India in patients with idiopathic hypoPT. ( 17 , 27 ) Mortality was not reported to be increased in Denmark or South Korea, despite the increased morbidity these patients experience from recognized complications, but was increased in Scotland and Sweden.…”
Section: Introductionmentioning
confidence: 99%